2017
DOI: 10.1007/s00586-017-5230-4
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of low-dose and high-dose tranexamic acid in posterior lumbar interbody fusion: a double-blinded, placebo-controlled randomized study

Abstract: Level 1 study according to Oxford Centre for Evidence-Based Medicine 2011 Levels of Evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 34 publications
2
27
0
Order By: Relevance
“…Low dose (5 mg/kg of bolus loading dose and 1 mg/kg of continuous infusion until 5 h after surgery) and high dose (10 mg/kg of bolus loading dose and 2 mg/kg of continuous infusion until 5 h after surgery) of TXA were applied for single-level posterior lumbar interbody fusion, and 24 cases were included in each group. The results found that TXA resulted in the significant decrease in intraoperative blood loss (385 ± 139 ml versus 542 ± 333 ml in the control group, P = 0:03), but there was no statistical difference between the low dose of TXA and the control group (508 ± 269 ml versus 542 ± 333 ml, P = 0:74), indicating that high dose of TXA was effective to reduce blood loss for posterior lumbar interbody fusion [18]. Considering the outcomes including Hb and HCT, high dose of TXA and control intervention resulted in similar change of Hb (1:3 ± 0:6 versus 1:7 ± 0:2 g/dl, respectively, P = 0:75) and HCT (2:3 ± 1:6 versus 5:8 ± 2:3%, respectively, P = 0:15) [18], which was also confirmed by another study involving 50 patients in the TXA group and 46 patients in the control group for posterior lumbar surgery [17].…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Low dose (5 mg/kg of bolus loading dose and 1 mg/kg of continuous infusion until 5 h after surgery) and high dose (10 mg/kg of bolus loading dose and 2 mg/kg of continuous infusion until 5 h after surgery) of TXA were applied for single-level posterior lumbar interbody fusion, and 24 cases were included in each group. The results found that TXA resulted in the significant decrease in intraoperative blood loss (385 ± 139 ml versus 542 ± 333 ml in the control group, P = 0:03), but there was no statistical difference between the low dose of TXA and the control group (508 ± 269 ml versus 542 ± 333 ml, P = 0:74), indicating that high dose of TXA was effective to reduce blood loss for posterior lumbar interbody fusion [18]. Considering the outcomes including Hb and HCT, high dose of TXA and control intervention resulted in similar change of Hb (1:3 ± 0:6 versus 1:7 ± 0:2 g/dl, respectively, P = 0:75) and HCT (2:3 ± 1:6 versus 5:8 ± 2:3%, respectively, P = 0:15) [18], which was also confirmed by another study involving 50 patients in the TXA group and 46 patients in the control group for posterior lumbar surgery [17].…”
Section: Discussionmentioning
confidence: 93%
“…Only two RCTs reported the impact of preoperative and intraoperative intravenous infusion of TXA on blood loss for spinal fusion surgery [17,18]. Intravenous tranexamic acid might have the better ability to reduce blood loss than its local infiltration [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…e optimal dosage and application of TXA has been a hot topic in clinical discussion. In one study, the high-dose and low-dose groups received 10 and 5 mg/kg of bolus loading dose and 2 and 1 mg/kg of continuous infusion until 5 h after surgery [31].…”
Section: Postoperative Aptt (Seconds)mentioning
confidence: 99%